An analysis on transmission of ethnic languages in selected communities in the world heritage site of Malacca, Malaysia - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Bachok, Syahriah; Ibrahim, Mansor (Elsevier, 2014)
This paper reviews an analysis on transmission of Ethnic Languages of selected cultural communities in one of the World Heritage Sites, Malacca. Ethnic Language is one of the most valuable Intangible Cultural Heritage recognized in UNESCO Convention of Safeguarding Intangible Cultural Heritage in 2003. Survey Questionnaires conducted with the selected cultural communities intend to determine the level of Intangible Cultural Heritage manifestation. The survey inquiries adopted five domains of Intangible Cultural Heritage recognized by UNESCO. The domains are Oral Tradition, Performing Arts, Knowledge, Social Practices and Traditional Craftsmanship. The analyses found that there are two significant factors influencing the level of Intangible Cultural Heritage manifestation as well as in transmission of Ethnic Languages. The first factor is the influence of intertwining Intangible Cultural Heritage manifestations. The second factor is the unfavorable influence of universal culture. Concurrently, the recommendations highlight on important Intangible Cultural Heritage to be enhanced in order for the threatened and declining Intangible Cultural Heritage to be safeguarded. The recommendations also generate approaches to overcome the unfavorable influence of universal culture on local culture in the attempt to safeguard Intangible Cultural Heritage as well as to improve the transmission of Ethnic Languages.